DAMAI Bersama Al-Quran / gambar, Abdul...[et.al]; cerita, Al-Farabi Alma Putra...[et.al]; penyunting ilustrasi, Rony Amdani; penyunting naskah, Wiwit Wijiastuti - Rony Amdani; Wiwit Wijiastuti; Al-Farabi Alma Putra; Abdul (Muffin Graphics, 2017)
94 hlm. : ilus. ; 21 cm.